2012
DOI: 10.1002/ece3.363
|View full text |Cite
|
Sign up to set email alerts
|

Climate‐change refugia in the sheltered bays of Palau: analogs of future reefs

Abstract: Coral bleaching and mortality are predicted to increase as climate change-induced thermal-stress events become more frequent. Although many studies document coral bleaching and mortality patterns, few studies have examined deviations from the expected positive relationships among thermal stress, coral bleaching, and coral mortality. This study examined the response of >30,000 coral colonies at 80 sites in Palau, during a regional thermal-stress event in 2010. We sought to determine the spatial and taxonomic na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
172
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(191 citation statements)
references
References 49 publications
17
172
0
2
Order By: Relevance
“…Consequently, unless corals can be protected by refuge environments, it will be the collective suite of available traits of the coral holobiont that determine its adaptive capabilities and ultimate survival. As such, understanding the full suite of traits available for corals to trade-off for survival is imperative to assessing the future vulnerability of species, and ultimately shifts in community structure and function (Table 1) (van Woesik et al, 2012). Caution must therefore be taken in assessing single traits and using these to make statements on acclimation and/or adaptive potential (e.g., Suggett et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, unless corals can be protected by refuge environments, it will be the collective suite of available traits of the coral holobiont that determine its adaptive capabilities and ultimate survival. As such, understanding the full suite of traits available for corals to trade-off for survival is imperative to assessing the future vulnerability of species, and ultimately shifts in community structure and function (Table 1) (van Woesik et al, 2012). Caution must therefore be taken in assessing single traits and using these to make statements on acclimation and/or adaptive potential (e.g., Suggett et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Cacciapaglia and van Woesik (2015) predicted that 9% of coral environments previously considered uninhabitable under ocean warming, due to the combination of elevated temperatures and high irradiance, would be protected by the mitigating effect of shading in high turbid sites. Studies in Palau (van Woesik et al, 2012), Florida (van Woesik and McCaffrey, 2017), and on the GBR (Morgan et al, 2017) have all provided compelling evidence that coral bleaching can be reduced at high-turbidity sites. Consequently, as the oceans warm and bleaching events become more frequent, there could be a direct selection of corals able to survive in inshore turbid environments (van Woesik and McCaffrey, 2017).…”
Section: Turbid Reefsmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have shown, however, that the in situ temperatures of nearshore waters at the local or reef scale (, 1 km) can deviate significantly from the temperature of offshore waters (Leichter et al 2006;Castillo and Lima 2010;Pineda et al 2013). Furthermore, spatial variations in water temperature and bleaching intensity within nearshore reef systems can occur over tens to hundreds of meters (Davis et al 2011;van Woesik et al 2012;Pineda et al 2013). Such small-scale variations in temperature and thermal stress could thus pose a challenge for predicting the bleaching or reduced growth of corals based solely on offshore sea surface temperatures (SST; McClanahan et al 2007;Maynard et al 2008;Weeks et al 2008).…”
mentioning
confidence: 99%
“…Likewise, the high diversity and abundance of corals found in shallow mangrove areas in St. John, US Virgin Islands, may persist in spite of high temperatures because of a combination of acclimatization to variable temperatures and shading by mangrove trees [168]. Van Woesik et al [180] observed that corals growing in more turbid waters in Palau bleached less in 2010 than those in clearer, offshore waters, although they experienced the highest temperatures. In Southeast Asia, reefs that bleached in 1998 and had higher temperature variability bleached less in 2010, showing the role that thermal history can play [129].…”
Section: Biodiversity and Resiliencementioning
confidence: 99%